The Brazilian Rare Genomes Project: Validation of Whole Genome Sequencing for Rare Diseases Diagnosis - Coelho, Antonio Victor Campos; Mascaro-Cordeiro, Bruna; Lucon, Danielle Ribeiro; Nóbrega, Maria Soares; Reis, Rodrigo de Souza; de Alexandre, Rodrigo Bertollo; Moura, Livia Maria Silva; Oliveira, Gustavo Santos de; Guedes, Rafael Lucas Muniz; Caraciolo, Marcel Pinheiro; Zurro, Nuria Bengala; Cervato, Murilo Castro; et al. (Frontiers in Molecular Biosciences, 2022)
Rare diseases affect up to 13.2 million individuals in Brazil. The Brazilian Rare Genomes Project is envisioned to further the implementation of genomic medicine into the Brazilian public healthcare system. Here we report the validation results of a whole genome sequencing (WGS) procedure for implementation in clinical laboratories. In addition, we report data quality for the first 1,200 real-world patients sequenced. We sequenced a well-characterized group of 76 samples, including seven gold standard genomes, using a PCR-free WGS protocol on Illumina Novaseq 6000 equipment. We compared the observed variant calls with their expected calls, observing good concordance for single nucleotide variants (SNVs; mean F-measure = 99.82%) and indels (mean F-measure = 99.57%). Copy number variants and structural variants events detection performances were as expected (F-measures 96.6% and 90.3%, respectively). Our WGS protocol presented excellent intra-assay reproducibility (coefficients of variation ranging between 0.03% and 0.20%) and inter-assay reproducibility (coefficients of variation ranging between 0.02% and 0.09%,). Limitations of the WGS protocol include the inability to confidently detect variants such as uniparental disomy, balanced translocations, repeat expansion variants, and low-level mosaicism. In summary, the observed performance of the WGS protocol was in accordance with that seen in the best centers worldwide. The Rare Genomes Project is an important initiative to bring pivotal improvements to the quality of life of the affected individuals.